Reading the hijab as a Marker of Faith in Randa Abdel- Fattah’s Does My Head Look Big in This? - Amrah Abdul Majid (Penerbit Universiti Kebangsaan Malaysia, 2016)
Randa Abdel-Fattah’s 2006 novel, Does My Head Look Big in This?, is about a teenage Australian Muslim protagonist who voluntarily chooses to wear the hijab to her elite private school in Melbourne, and the personal and social challenges that she faces after making this decision. In this paper, I suggest that the novel portrays the action of wearing the hijab as mainly apolitical, and that it is instead a spiritual and religious act which demonstrates aspects of the hijab as empowering to an individual’s life. This subverts the stereotypical understanding of the hijab, particularly by the West, as either a tool of control and subjugation of Muslim women, or as a stand against Western society and ideology. By using Saba Mahmood’s (2005) study of Muslim women piety, which argues that Islam and its practices can be used as a tool for women’s empowerment, particularly for achieving selfimprovement and self-actualization, this paper pays attention to the representation of the hijab in the novel. The decision to wear the hijab opens a path for the protagonist to become more adherent to her religion, as well as improving her attributes and individuality as a whole. This creates a wholesome young woman who is not only committed to her religion, but is also mindful of her character.